Liminal Spaces and Structural Limitations of First Nation Urban Reserves - Fawcett, R. Ben; Walker, Ryan; Belanger, Yale (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
Resolving urban land claims is an important facet of enacting sovereignty in cities and is occurring in the cities of settler states like Canada, Australia, and New Zealand. The creation of urban reserves is an important means by which First Nations in Canadian cities, especially on the Prairies, are settling outstanding land claims. Findings from interviews with key informants on the urban reserve creation process in Saskatchewan, Canada’s two largest cities, shows urban reserves as liminal spaces in dynamic tension between self-determination, jurisdiction, economic development, and colonial processes of property stipulation, government relations, and approval. This policy area can be enhanced at each stage of the process and offers a pathway toward active treaty relationships in cities.